2019
DOI: 10.1038/s41598-019-53487-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Labeling of Bone Microdamage in an Animal Model of Type 1 Diabetes Mellitus

Abstract: Type 1 diabetes mellitus (DM1) is linked to a decrease in bone strength. Bone strength entails both bone mineral density and bone quality. Limited data are available regarding diabetes-induced microdamage, which can severely influence bone quality. This study has investigated bone microdamage as a measure of bone quality in an animal model of DM1. Microdamage in the neck of the femur was labelled in vivo using multiple fluorochromes at 4, 12 and 24 weeks after the onset of DM1. Microcracks were quantified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(74 reference statements)
1
1
0
Order By: Relevance
“…Limirio et al also reported that bone biomechanical properties in diabetic rats are compromised due to the lack of proper collagen maturation, leading to loss of bone mineral content [10]. Mohsin at al referred that bone quality alterations in diabetic rats are even associated with the early stages of DM [55], being consistent with present study that establishes that the exposure to high glucose concentrations induces alteration on bone metabolism/development, even upon a short-term exposure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Limirio et al also reported that bone biomechanical properties in diabetic rats are compromised due to the lack of proper collagen maturation, leading to loss of bone mineral content [10]. Mohsin at al referred that bone quality alterations in diabetic rats are even associated with the early stages of DM [55], being consistent with present study that establishes that the exposure to high glucose concentrations induces alteration on bone metabolism/development, even upon a short-term exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were described within in vivo studies with rodents. Mohsin et al [55], and Silva et al [56] reported, in their works, that bone structure is affected in rats with DM, with decrease bone mechanical proprieties as result of decreased matrix mineralization. Limirio et al also reported that bone biomechanical properties in diabetic rats are compromised due to the lack of proper collagen maturation, leading to loss of bone mineral content [10].…”
Section: Discussionmentioning
confidence: 99%